Kinetic-magnetic energy exchanges in rotating magnetohydrodynamic turbulence. Issue 4 (3rd April 2019) - Baklouti, F. S.; Khlifi, A.; Salhi, A.; Godeferd, F.; Cambon, C.; Lehner, T.
ABSTRACT: We use direct numerical simulations to study the dynamics of incompressible homogeneous turbulence subjected to a uniform magnetic field B in a rotating frame with rotation vector Ω . We consider two cases: Ω ∥ B and Ω ⊥ B . The initial state is homogeneous isotropic hydrodynamic turbulence with Reynolds number R e = u l l / ν ≃ 170. The magnetic Prandtl number P m = ν / η = 1 and the Elsasser number Λ = B 2 / ( 2 Ω η ) = 0.5, 0.9 or 2. For both the cases Ω ∥ B and Ω ⊥ B, the total energy decays as ∼ t − 5 / 7 for Λ = 0.5 and 0.9, and as ∼ t − 6 / 7 for Λ = 2 . In the spectral range 2 <  k  < 20, the kinetic energy spectrum scales as ∼ k − p where p increases with time ( 2 ≤ p ≤ 4.2 ). This scaling is similar to that observed in quasi-static MHD. The two rotating MHD flow cases differ mainly in how kinetic and magnetic fluctuations exchange energy, with a mechanism mostly driven by the dynamics of the spectral buffer layer around k ∥ Ω = | Ω ⋅ k | / Ω ≈ 0 . At k ∥ Ω = 0, the inertial and Alfvén waves frequencies vanish when Ω ∥ B, but only the inertial waves frequency vanishes when Ω ⊥ B . When Ω ∥ B, rotation results in an increased reduction of magnetic fluctuations generation. In terms of anisotropy, we show that the elongated structures occurring in rapidly non-magnetised rotating flows are distorted or inhibited for Ω ⊥ B, and weakened for Ω ∥ B .